2010
DOI: 10.21273/hortsci.45.4.605
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Physicochemical Responses of ‘Sai Nam Phueng’ Tangerine to Commercial Coatings

Abstract: Tangerine fruit cv. Sai Nam Phueng was coated with six commercial coatings: Citrashine, Fomesa, Citrosol AK, Supershine-C, Zivdar, and Perfect Shine. Fruit were coated using gloved hands and stored at room temperature (23 ± 3 °C) and 56% ± 5% relative humidity. Physiological and chemical properties were recorded on Days 0, 1, 4, 7, 10, and 13. All coated fruit had lower respiration rates, reduced weight loss, higher gloss, and better appearance than control fruit. Coatings somewhat increased total solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The intensity of gas (CO2 and O2) change of fruits depends on the coating formulation and on the storage conditions of the products. Seehanam and Boonyakiat (2010) observed that the respiration rate of mandarin coated with some commercial coatings stored at room temperature was decreased over uncoated or control fruits. Das and Medhi (1996) reported that coconut oil and castor oil coating on pineapple closed the opening of stomata and lenticels results the reduction of transpiration rate, respiration rate and microbial activity.…”
Section: Discussionmentioning
confidence: 95%
“…The intensity of gas (CO2 and O2) change of fruits depends on the coating formulation and on the storage conditions of the products. Seehanam and Boonyakiat (2010) observed that the respiration rate of mandarin coated with some commercial coatings stored at room temperature was decreased over uncoated or control fruits. Das and Medhi (1996) reported that coconut oil and castor oil coating on pineapple closed the opening of stomata and lenticels results the reduction of transpiration rate, respiration rate and microbial activity.…”
Section: Discussionmentioning
confidence: 95%
“…As in many other citrus fruits, visual quality largely affects the marketability of limes where firm, mature green limes are highly appreciated by consumers (Rodrigo et al, 2013). According to the VQR scale of Seehanam et al (2010), fruits having a VQR below 3, was considered as unmarketable. VQR of fruits harvested 161 DAFS sharply declined from 4.29±0.18 at 3 DAS to 2.6±0.3 at 6 DAS exhibiting the shortest marketable period of 3 days (Figure 4 and late 1).…”
Section: Resultsmentioning
confidence: 99%
“…Fruits of uniform size that are free from defects and blemishes were selected from each maturity stage and stored under ambient conditions (30-34 °C, 70-75% RH) in medium size (600 x 300 x 320 mm) surface sterilized plastic crates with Bleach (NaOH). The physical, physiological and biochemical quality attributes were evaluated at harvest (day 0) and were proceeded at 3 day intervals until the produce indicated the limit of the marketability, according to visual quality rating (VQR) chart developed by Seehanam et al (2010). Peel colour was measured by hunter lab colour difference meter (CR 400 -Konica, Minolta) in terms of lightness (L*), a* and b* values and thereby hue angle ((h o : arc tan (b*/a*)) and Chroma (C: [(a*) 2 + (b*) 2 ] ½ ) were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-transpiration, acting as a barrier between the surrounding environment and the fruit's tissues, can modify the internal atmosphere of the fruit by reducing the concentration of oxygen and increasing the concentration of carbon dioxide. This, in turn, increases carbon dioxide solubility and accumulation during fruit respiration, contributing to the variation in the total acidity percentage [27]. Anti-transpiration has been shown to reduce the respiratory rate [28].…”
Section: Discussionmentioning
confidence: 99%